A review of leadership moral ethics in the 21st century: a South African perspective - Msiza, M. L.; Mthembu, N. (My University, 2020)
Since the dawn of 1990s, social change in South Africa has provided a series of opportunities to government and related institutions of learning with a view to alter social structures and practices that were perceived to adhere to a narrow cultural perspective. However, despite the adoption of the Ubuntu moral ethics as a guiding philosophy in rendering the required change in service delivery and related Public administration, the reality tends to suggest that related Public Administration seems to be limited when it comes to evoking or apply the related Ubuntu principle in their daily practice. Furthermore, traditional management fundamentals remain observable; the notions of workers and management remain the mainstay of the practice. In view of these limitations, this chapter intends to highlight some of the challenges that limit the present Public Administration in effectively perfecting their mandate in their respective social spheres in particular in realization of multicultural management practice. Again, literature review will be explored to identify current challenges that affect general Public Administration and governance in various social structures in relation to redressing the past injustices. These experiences can be related to the present continuous marginalization of the indigenous value systems such as Ubuntu and the decay of moral ethics in view of the increase in the number of reported corruption related incidences. In view of the fact that a success of a sound programme and its implementation depends on the quality of Public Administration; this chapter concludes that only Public Administration with relevant skills in terms of being knowledgeable of multicultural perspectives in particular when it comes to understanding diverse ethics value systems. Finally, the success of transformation agenda in terms of redressing the past injustices and incorporation of indigenous African value systems in all social spheres in South Africa depends on the education system that respects all people's values systems equally and geared to enhance multicultural society.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Administration; Leadership; Morals; Public; Private; Ubuntu; Leadership -- South Africa; Public administration -- South Africa; Ethics